2023
DOI: 10.1007/s00406-022-01537-y
|View full text |Cite
|
Sign up to set email alerts
|

Tübinger Training for Autism Spectrum Disorders (TüTASS): a structured group intervention on self-perception and social skills of children with autism spectrum disorder (ASD)

Abstract: In autism spectrum disorders (ASD), social communication and stereotypical behaviour patterns affect all areas of life, and can result in a decrease of its quality. Previous research has shown promising results for the social skills of groups of children with ASD. Furthermore, a pilot study of the Tübingen Group Training for Autism Spectrum Disorders (TüTASS) has demonstrated that mindfulness-based elements achieve additional positive effects. To build on these findings, the TüTASS training was adapted and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Regardless, top to bottom examinations revealed that the augmentations were somewhat modest.it was presumed that AAC mediations don't seem to impede talk age and may bring about extended talk creation, the modest expands viewed require down to earth desires among clinicians and various accomplices. Future research should be more theory driven and intend to perceive perceptive members characteristics, for instance, prior talk pantomime and article examination tendency 12,13 .…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, top to bottom examinations revealed that the augmentations were somewhat modest.it was presumed that AAC mediations don't seem to impede talk age and may bring about extended talk creation, the modest expands viewed require down to earth desires among clinicians and various accomplices. Future research should be more theory driven and intend to perceive perceptive members characteristics, for instance, prior talk pantomime and article examination tendency 12,13 .…”
Section: Discusionmentioning
confidence: 99%
“…In 2019 the research was held on the many youngsters with mental imbalance inaccessible escalated guidance in the utilization of intensifying or elective correspondence frameworks 12,13 , for example, picture-exchange messaging system (PECS). The examination explored the utilization of PECS with three young men with autism to decide the effect of PECS preparing on utilization of images for mentioning, utilization of clear symbols, and dysfunctional practices.…”
Section: Discusionmentioning
confidence: 99%